ANALISIS KESULITAN DALAM MENYELESAIKAN SOAL BARISAN DAN DERET GEOMETRI SISWA SEKOLAH MENENGAH ATAS - Isnaini, Ade Nur; Mahardika, Arsyi Pramudya; Aditya, Bagas; Napis, Napis (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to determine the difficulties students experience in working on problems on geometric sequences and series. The type of research used is descriptive qualitative. The subjects studied were 10 students of class X-5 SMA Putra Bangsa, Depok City, based on the results of daily tests that were below the Minimum Completion Minimum (KKM). The test was given as many as 5 essay questions in the form of stories. The results of the study showed that the causes of difficulties experienced by students in solving geometric sequences and series problems included: 1) difficulties in distinguishing geometric sequences and series problems, 2) difficulties in understanding the intended problem and difficulties in translating it into mathematical sentences, 3) difficulties in solving problems related to geometric sequences and series material, sometimes students are confused by the questions asked in the problem, 4) students' difficulties when answering questions and entering formulas. This is as from the analysis it is known that the highest percentage of students' difficulties in solving story problems on geometric sequences and series reaches 71%. ABSTRAK Penelitian ini bertujuan untuk mengetahui kesulitan siswa dalam mengerjakan soal pada materi barisan dan deret geometri. Adapun jenis penelitian yang digunakan adalah deskriptif kuallitatif. Subjek yang diteliti adalah siswa kelas X-5 SMA Putra Bangsa Kota Depok sebanyak 10 siswa berdasarkan pada hasil ulangan harian yang berada dibawah KKM. Tes diberikan sebanyak 5 butir soal essay berbentuk cerita. Hasil penelitian menunjukan bahwa penyebab kesulitan yang dialami siswa dalam menyelesaikan soal barisan dan deret geometri diantaranya: 1) kesulitan dalam membedakan soal barisan dan deret geometri, 2) kesulitan memahami soal yang di maksud dan kesulitan dalam menerjemahkan kedalam kalimat matematika, 3) kesulitan dalam menyelesaikan soal berkaitan dengan materi barisan dan deret geometri terkadang siswa terkecoh dengan pertanyaan yang ditanyakan pada soal, 4) kesulitan siswa pada saat menjawab soal dan memasukan rumus. Hal ini sebagaimana dari analisis diketahui bahwa presentase tertinggi kesulitan siswa dalam melakukan penyelesaiann soal cerita pada barisan dan deret geometri mencapai 71% .